2015
DOI: 10.1111/bld.12142
|View full text |Cite
|
Sign up to set email alerts
|

Using repertory grid techniques to measure change following dialectical behaviour therapy with adults with learning disabilities: two case studies

Abstract: Accessible summary• Dialectical behaviour therapy (DBT) can be adapted for individuals with learning disabilities. DBT aims to teach people how to control their feelings, communicate with other people, manage distress and be more self-aware.• This article presents the case studies of two adults with learning disabilities who completed DBT and shows how their opinions of themselves and others changed.• The results discussed include overall change in construing, changes in self-esteem and changes in dilemmas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Sakdalan et al (2010) Both Brown et al (2013) and Lew et al (2006) incorporated specific training for support staff as part of the intervention, although additional information about the nature of this training, and the possible impact this may have had on outcomes was not included. McNair et al (2016a) found significant changes in self-esteem and resolution in personal dilemmas and a reduction in self-reported self-harm for their two participants. The variability of the interventions included in these papers appears idiosyncratic and most studies did not provide a specific rationale for inclusion or exclusion of the different components of DBT.…”
Section: Adapting Dbt For People With An Intellectual Disabilitymentioning
confidence: 83%
See 3 more Smart Citations
“…Sakdalan et al (2010) Both Brown et al (2013) and Lew et al (2006) incorporated specific training for support staff as part of the intervention, although additional information about the nature of this training, and the possible impact this may have had on outcomes was not included. McNair et al (2016a) found significant changes in self-esteem and resolution in personal dilemmas and a reduction in self-reported self-harm for their two participants. The variability of the interventions included in these papers appears idiosyncratic and most studies did not provide a specific rationale for inclusion or exclusion of the different components of DBT.…”
Section: Adapting Dbt For People With An Intellectual Disabilitymentioning
confidence: 83%
“…McNair et al. () found significant changes in self‐esteem and resolution in personal dilemmas and a reduction in self‐reported self‐harm for their two participants. The variability of the interventions included in these papers appears idiosyncratic and most studies did not provide a specific rationale for inclusion or exclusion of the different components of DBT.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Early case studies utilizing DBT techniques with PWID and BPD (Esbensen & Benson, ; Mavromatis, ; Wilson, ) reported marked improvements in aggressive and self‐injurious behaviours; however, conclusions on the effectiveness of DBT as a standalone intervention were precluded. More recently a pre–post case series delivering fully adapted DBT programmes reported significant reductions in aggression, risk‐taking and/or self‐harm (Brown, Brown, & Dibiasio, ; Charlton & Dykstra, ; Lew, Matta, Tripp‐Tebo, & Watts, ; McNair, Woodrow, & Hare, ) and the prevention of community placement breakdown (Baillie & Slater, ). An unpublished study of adapted DBT by McNair () found significant reductions in levels of depression, anxiety and anger, and significantly improved mindfulness skills, yet participants’ anxiety remained within the clinical range.…”
Section: Introductionmentioning
confidence: 99%